1990
DOI: 10.1523/jneurosci.10-01-00351.1990
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuits mediating visual flight control in flies. II. Separation of two control systems by microsurgical brain lesions

Abstract: The role of 2 sets of interneurons in the optic lobes of blowflies in visual course control was studied by means of brain lesions. The first set comprises the cells HS and H2, which respond to global horizontal motion. The second set are the FD-cells, which respond selectively to local horizontal motion. All these cells are output neurons of the third optic ganglion of flies and are thought to be coupled via descending neurons to the flight motor system. In 2 series of experiments specific cells of these 2 set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 31 publications
(21 reference statements)
1
36
0
Order By: Relevance
“…In the rear part of the third visual ganglion, the so-called lobula plate, there resides a set of 50-60 individually identifiable interneurons (Fig, 2) which receive input from retinotopically arranged arrays of local motion-sensitive elements (Dvorak et al, 1975;Pierantoni, 1976;Hausen, 1976;Hausen et al, 1980;Hengstenberg et al, 1982;Hengstenberg, 1982;Borst and Egelhaaf, 1992). From various lines of evidence it is concluded that they are involved in the fly's course control (Geiger and N~issel, 1981;Geiger and N~issel, 1982;Hausen and Wehrhahn, 1983;Hausen and Wehrhahn, 1990;Heisenberg et al, 1978). In different representatives of these cells the phenomenon of gain control was studied (Hausen, 1982;Egelhaaf, 1985;Haag et al, 1992)leading to the following result ( Fig.…”
Section: Gain Control In Behavior and Motion-sensitive Cellsmentioning
confidence: 99%
“…In the rear part of the third visual ganglion, the so-called lobula plate, there resides a set of 50-60 individually identifiable interneurons (Fig, 2) which receive input from retinotopically arranged arrays of local motion-sensitive elements (Dvorak et al, 1975;Pierantoni, 1976;Hausen, 1976;Hausen et al, 1980;Hengstenberg et al, 1982;Hengstenberg, 1982;Borst and Egelhaaf, 1992). From various lines of evidence it is concluded that they are involved in the fly's course control (Geiger and N~issel, 1981;Geiger and N~issel, 1982;Hausen and Wehrhahn, 1983;Hausen and Wehrhahn, 1990;Heisenberg et al, 1978). In different representatives of these cells the phenomenon of gain control was studied (Hausen, 1982;Egelhaaf, 1985;Haag et al, 1992)leading to the following result ( Fig.…”
Section: Gain Control In Behavior and Motion-sensitive Cellsmentioning
confidence: 99%
“…FD-cells are output elements of the lobula plate and project into the lateral protocerebrum where they probably synapse on descending neurons. FD-cells have been suggested to play a crucial role in mediating object-directed turning responses (Egelhaaf 1985a,b,c;Egelhaaf et al 1988;Reichardt et al 1989;Hausen and Wehrhahn 1990). It has been suggested recently that, in addition to the FD-cells described by Egelhaaf (1985b), further types of¯y TCs exist which also exhibit small-®eld-tuning (Gauck and Borst 1999).…”
Section: Introductioǹmentioning
confidence: 99%
“…A number of LPTCs have properties consistent with cells that process higher-order motion, such as the figure-detecting (FD) cells. FD cells respond to the motion of small objects in their receptive fields and are thought to support object fixation behavior (Egelhaaf, 1985a,b;Hausen and Wehrhahn, 1990). Flies produce yaw optomotor responses when challenged with second order motion which are not fully accounted for by integrated EMD signals alone (Theobald et al, 2008).…”
Section: Discussionmentioning
confidence: 99%